Online Political Communication How to Use the Web to Build Consensus and Boost Participation - Giansante, Gianluca; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book provides research findings and practical information on online communication strategies in politics. Based on communication research and real-world political-campaign experience, the author examines how to use the Web and social media to create public visibility, build trust and consensus, and boost political participation. It offers a useful guide for practitioners working in the political arena, as well as for those managing communication projects in institutions or companies.
Foreword -- 1 Introduction -- 2 How Politics Change on the Web -- 3 Building an Online Communication Strategy -- 4 Online Communication Tools -- 5 Producing Content That Creates Participation and Consensus.
Keywords: Political communication; Communication; Public relations; Sociology; Political Communication; Communication Studies; Corporate Communication/Public Relations; Media Research